(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In the strengthening of democratic and strategic reforms in the Republic of Uzbekistan, the spiritual heritage, national values and traditions of our people, and the future of our youth, are of great importance. This article provides information on the development of spiritual awareness in our people and youth, and the formation of immunity against foreign ideas affecting spirituality. We organized a discussion with experienced pedagogues-psychologists in our country about the factors affecting the morale of our youth, and we listened to their opinions. The first president of the Republic of Uzbekistan I. Karimov’s work "High Spirituality - Invincible Power" contains the opinions that have gained importance in improving the spiritual maturity of our youth.